Strategi Pemasaran Pada Caffee Ten Bos Boba Simpang Tiga Ngalam Kabupaten Seluma - Sherin Dwi Julia; Rina Trisna Yanti; Nirta Vera Yustanti (UNIVED Press, 2023)
The purpose of this study was to determine the marketing strategy of Caffee Ten Bos Boba Simpang Tiga Ngalam, Seluma Regency. This study used a qualitative descriptive research method with data collection techniques using questionnaires. The analytical technique used is SWOT (Strengths Weakness Opportunities and Threats) analysis in determining the cafe's internal and external factors formulated through SAP (Strategic Advantage Profile) and ETOP (Environmental Threat and Opportunity Profile). The results of the SWOT analysis, Caffee Ten Bos Boba Simpang Tiga Ngalam, Seluma Regency is in an investment position which is the interaction of the results of SAP (strategic profile analysis) obtained a value of 4.13 with a strong position and from the results of ETOP analysis (Environmental Threat Opportunity Profile) obtained a value of 3 .95 for opportunities and threats 2.29 which shows the company's position in a speculative business.